2012
DOI: 10.1111/j.1538-7836.2012.04862.x
|View full text |Cite
|
Sign up to set email alerts
|

PROC c.574_576del polymorphism: a common genetic risk factor for venous thrombosis in the Chinese population

Abstract: See also Hamasaki N. Unmasking Asian thrombophilia: is APC dysfunction the real culprit? This issue, pp 2016–8. Summary.  Background:  There are ethnic differences in the genetic risk factors for venous thrombosis (VT). The genetic causes of VT in the Chinese population are not fully understood. Objectives:  To identify possible common abnormal factors that could contribute to thrombosis susceptibility. Methods/Results:  We measured the levels of nine types of plasma coagulation factor, three types of anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 52 publications
5
65
3
Order By: Relevance
“…In China, two recent studies found two predominant mutations of PROC, Lys173del and Arg189Trp, both in VTE patients and in the general population (Table 3). 32,33 In our study, Lys173del and Arg189Trp were observed in three and one patients, respectively, but not in the population group ( Figure 1A). Of note, all three patients with heterozygous Lys173del also had another PROC mutation (Table 2).…”
contrasting
confidence: 58%
See 2 more Smart Citations
“…In China, two recent studies found two predominant mutations of PROC, Lys173del and Arg189Trp, both in VTE patients and in the general population (Table 3). 32,33 In our study, Lys173del and Arg189Trp were observed in three and one patients, respectively, but not in the population group ( Figure 1A). Of note, all three patients with heterozygous Lys173del also had another PROC mutation (Table 2).…”
contrasting
confidence: 58%
“…Since Lys173del does not result in a significant decrease of the amidolytic activity of PC, it is plausible that any heterozygous carriers of Lys173del in the patient or population group would have been missed in this study. 33 Studies from Western countries have shown that PC deficiency is the most frequent natural anticoagulant deficiencies in VTE patients, followed by PS and AT deficiency, with limited reports on predominant mutations. 2,9 Ala416Ser (or Ala384Ser) of SERPINC1 (antithrombin Cambridge II) was reported to be frequent both in VTE patients and in the general population in Britain, while it was not detected in China.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In 92 term newborns with ischemic strokes [8], 62 patients (68%) had at least one prothrombotic risk factor compared with 44 controls (24%), and PC-type I deficiency was found in 6 neonates. Table 1 shows the summary of heritable PC-deficiency associated with fetal ventriculomegaly [3,5,6]. Four reported patients were considered to carry the biallelic mutation.…”
Section: Discussionmentioning
confidence: 98%
“…Direct sequencing of the coding and promoter regions of PROC determined a heterozygous mutation in exon 7 of PROC c.574_576delAAG, p.Lys193del in both the infant and his healthy father. The 3-base deletion raises the thromboembolic risk in Japanese [5] and Chinese populations [6]. The infant had no explainable causes of ventriculomegaly and infarction other than the deletion, although PC-activity of his father was 100% (one time study).…”
Section: Case Reportmentioning
confidence: 98%